The porcelain moon : a novel of France, the Great War, and forbidden love - Chang, Janie (William Morrow, an imprint of HarperCollinsPublishers, 2023)
In 1918 France, in the final days of the First World War, Pauline Deng, a young Chinese woman escaping an arranged marriage, is taken in by secretive Camille Roussel and becomes bound to this woman forever when they are forced to make a terrible decision.